Social Media Addiction and Fear of War in Germany - André Hajek; Benedikt Kretzler; Hans-Helmut König (Psychiatry International, 2022)
Individuals with an excessive use of social media may be frequently exposed to stimuli, such as (fake) news or images of violence, which might lead to a higher fear of war. Therefore, the objective of this study is to examine the association between a social media addiction and fear of war (conventional war and nuclear war) in Germany. Data were taken from a nationally representative survey with n = 3091 participants (18 to 74 years; data collection in mid-March 2022). Social media addiction was quantified using the validated Bergen Social Media Addiction Scale. Moreover, established items were used to quantify a fear of war. Medium differences (in terms of Cohen’s d) were identified regarding the fear of war between individuals without a social media addiction and individuals with a social media addiction. Adjusting for several covariates, the regressions revealed that individuals with a social media addiction had a higher fear of war compared to individuals without a social media addiction (fear of a conventional war: β = 0.44, p < 0.01; fear of a nuclear war: β = 0.61, p < 0.001). In conclusion, our study demonstrated an association between a social media addiction and fear of war.